Quiezzz..

Posted on

_________
1.) 5(y + 2x – 3z) = …?
2.) 5(x² -xy + x) = …?

LAGEHHHH??

Quiezzz..

Jawaban:

5(y + 2x - 3z)

(5×y)(5×2x)(5×(-3z))

 = 5y + 10x - 15z

#❁#❁#❁#❁#❁#❁#❁#❁#❁#❁#❁#

5( {x}^{2} - xy + x)

(5×{x}^{2})(5×(-xy))(5×x)

 = {5x}^{2} - 5xy + 5x

#❁#❁#❁#❁#❁#❁#❁#❁#❁#❁#❁#

koreksi jika salah

sekian dan terima kasih

 boxed{ colorbox{ccddff}{by : anditapratiwi796}}

Penyelesaian No.1

5(y + 2x 3z) = . . . ?

tt5(y + 2x - 3z) = ... \ tt = (5 times y) + (5 times 2x) + (5 times ( - 3z) \ tt = 5y : + 10x : + : ( - 15z) : : : : : : : : : : : : : : : : : : : \ tt = 5y : + : 10x : - 15z : : : : : : : : : : : : : : : : : : : : : : : : :

Penyelesaiannya No.2

5( xy + x) = . . . ?

tt5( {x}^{2} - xy + x) = ... \ tt = (5 times {x}^{2} ) + (5 times ( - xy)) + 5 times x) \ tt = {5x}^{2} + ( - 5xy) + 5x : : : : : : : : : : : : : : : : : : : : : : \ tt = {5x}^{2} - 5xy + 5x : : : : : : : : : : : : : : : : : : : : : : : : : : : :